PEMBELAJARAN BAHASA JEPANG PERHOTELAN BIDANG TATA HIDANGAN BERBASIS ROLE PLAYING PADA PROGRAM STUDI DIPLOMA IV PERHOTELAN UNIVERSITAS TRIATMA MULYA - Anak Agung Ratih Wijayanti; Isa Wahjoedi Dwi Poetranto; Sulistyo Adi Joko Saharjo (Journal of Tourism and Interdiciplinary Studies, 2022)
Japanese language used in the hotel industry requires students to use Japanese Language according to department in the hotel. Students in the Diploma IV Hospitality study program are prepared to become hoteliers who can provide services to guests using Japanese Language based on hotel service standards, which is in food and beverage.This study aims to determine the role playing-based teaching Japanese Hospitality at Food and Beverage Department in the Diploma IV Hospitality study program at Triatma Mulya University and to find out the obstacles found in the application of the role playing. The number of students who participated in the study was 26 people. This research uses the observation method to observe the learning process of Japanese Hospitality at Food and Beverage Department. Based on the results of the study, hospitality Japanese learning was applied using conversation scenarios between staff and guests who communicated about how to welcome guests at the restaurant, conversations in situations where guests were taken to their seats, provided menus, explained recommended menus, and asked for impressions and messages from guests. The obstacles in learning are inappropriate gestures and intonations during role play in Japanese Language.